"The greatest extravaganza of mortal combat ever staged" - Daniel Vella (Eludamos)
This paper examines the dystopian Italian science-fiction film I guerrieri dell’anno 2072 (Fulci, 1984), with a particular focus on the Battle of the Damned, a deadly televised contest in which condemned prisoners fight to the death in the reconstructed Colosseum in Rome. A consideration of this fictional game within the film’s dystopian future Rome will open onto three intertwined lines of analysis: the classicist impulse to conceive of a continuity between imperial Rome and contemporary Italy, the adoption of this classicism in fascist Italy, and media consolidation in the context of neoliberalism and political corruption in the 1980s. By pursuing these lines of analysis, the paper will argue that Fulci’s film functions as a critique of the national cultural moment from which it looks towards both Italy’s past and future as a continuity of authoritarianism and oppression.